Local brand mobile shopping application prototype (LBMSAP) / Nur A'zimah Hanim Mhd Nasir - Nur A'zimah Hanim, Mhd Nasir (2016)
Local Brand Mobile Shopping Application Prototype (LBMSAP) is a system mobile application online shopping for Malaysia local product only. The aim for this project is to help our traders publish their product in this application. This system also can be mediation traders to customer for publish their product. As a result, the customer can know the Malaysia product brand. The LBMSAP system only focuses some type product in area fashion, gajet and kraftangan. This system only focuses for some product because from the research fashion and gajet is a highest priority buyer online. Furthermore, kraftangan products also added in this system to promote local brand products mainly to Malaysians citizen onward to other countries. The main users that involve in this system are trader and customer. The traders can add the news of their product in these systems to advertise. This information will give the interactive way to book product. The trader can give the best service in advertise their product. Besides that, the traders help their product to introduce foreign customer and especially local customer in Malaysia. The customer also can get information from the trader’s news product in using system mobile application. These allow customer facilitate process purchases. Besides that, customer can easily to know the Malaysia product. The customer more wise make choose in purchase the quality Malaysia product. The system also can simplify traders and customers to view, insert, and communicate with their product. Additional features will add on to this system is add some types in the system and make calculation buying for customer section. Last result from users observation in research, they agree this system should have to give information about Malaysia product brand.